EU competition law and internal energy market - García Coso, Emiliano (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This article focuses on the application of EU competition rules as a complementary and essential instrument of the energy regulatory framework with the aim of guaranteeing and achieving the internal energy market. The peculiarities of the energy market need to be explored from their consideration as manifestations that can alter the objectives of Competition Law and, therefore, must be subject to the application of its regulations, considering the decisions of the Commission and the CJEU jurisprudence. The characteristics and actors in the internal energy market reveal areas of action that can be considers as agreements and practices that restrict competition, behaviors that represent an abuse of a dominant position in the energy market, with state aid systems incompatible with its legal regime and with the carrying out of operations that may violate the Merger Regulation.
Keywords: internal Energy Market; Competition; restrictive agreements; abuse of a dominant position; state aid; merger; electricity and gas